Relasi Sosial Nelayan Suku Bajo - Radiallahu, Muh. Rifaldi Radiallahu; Marhadi, Akhmad (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research aims to determine: the social relations between collectors and catch fishermen in Torokeku Village, as well as to find out the importance of social relations formed between catch fishermen and collectors in Torokeku Village. This research uses social capital theory according to Francis Fukuyama. The method in this research is ethnography with a data collection method combining participant observation techniques and in-depth interviews. The community environment in Torokeku Village, Tinanggea District, has relationships that occur, starting from one individual to another. The results of the research show that the social relations between collectors and fishermen in Torokeku Village go through several things; First, accounts payable. Fishermen in Torokeku Village have practiced paying debts to collectors so they can carry out fishing activities. There are several fishermen who practice debt and receivables in Torokeku Village, namely, collectors with fishermen who catch fish, collectors with fishermen who catch crabs, and collectors with fishermen who catch sea cucumbers. Second, buying and selling. Buying and selling between collectors and fishermen who catch fish, collectors and fishermen who catch sea cucumbers, and collectors and fishermen who catch crabs. Apart from that, the lives of fishermen are not free from reciprocal relationships, such as between collectors and captured fishermen who always form a bond or relationship that occurs continuously. The relationship that exists is based on each other's abilities and expertise with agreed terms. Social relations between collectors and fishermen in Torokeku Village are formed by several factors, namely supporting factors such as being influenced by ethnic relations, kinship, trust, friendship, neighbor relations and professional factors.